DETERMINATION OF LEVEL OF DRIED CAPSICUM POWDER FOR OPTIMISATION OF SPENT BROILER BREEDER HEN CHICKEN KOFTAS - M.V. Sneha Sharada; J. Indumathi; G. V. Bhaskar Reddy; S. Shakila (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was undertaken to evaluate the effect of different levels of dried capsicum powder on the quality characteristics of chicken koftas. The capsicum dried powder was incorporated at three different levels viz. 2, 4 and 6% in the formulation. The products were analyzed for various physicochemical and sensory attributes. The pH, emulsion stability (83.56±0.011) (%), cooking yield (81.12±0.011) (%), crude protein, crude fat and total ash contents of the products showed significant (P